Réponses

2014-10-16T14:12:08+02:00
exercice 3
A = (x-4)(x-4) - (x-2)(x-8)
A = (x
² - 4x - 4x + 16) - (x² - 2x - 8x + 16)
A = (x
² - 8x + 16) - (x² - 10x + 16)
A = x
²-x²-8x+10x+16-16
A = 2x
9996*9996 - 9998*9992 = (10000-4)(10000-4) - (10000-2)(10000-8)
remplaçons x par 10000
il vient 9996*9996 - 9998*9992 = 2*10000 = 20000
exercice 4
a)
E = (2x+3)2 + (x-7)(2x+3)
E = (2x+3)(2x+3) + (x-7)(2x+3)
E = 4x
² + 12x + 9 + 2x² -14x + 3x - 21)
E = 6x
² + x - 12
b) Mettons (2x+3) en facteur commun
E = (2x+3)(2x+3+x-7)
E = (2x+3)(3x-4)